Heterogeneity, politics of ethnicity, and multiculturalism; What is a viable framework for Indonesia? - Lan, Thung Ju (Wacana, Journal of the Humanities of Indonesia, 2011)
Indonesia is a plural society that consists of several hundred ethnic and sub-ethnic groups. One of its generic characteristics is heterogeneity. In the last ten years after the implementation of regional autonomy, we have witnessed the emergence of strong ethnic and religiously flavoured local identity politics in various places in Indonesia that created open and vicious conflicts. This periodical violence exploded especially during the election of district and provincial heads. The intimate relation multiculturalism, with the actual political praxis of everyday life as an alternative to the existing paradigm of the "homogenization" of nationhood, has not been discussed. I believe it is time to discuss the strategic junctures between heterogeneity, politics of ethnicity (and religion) and multiculturalism as well as their possible realization at the local and national levels in order to find a viable framework for a future Indonesia.